Online Assessment of Control-Based System Security and Stability Service Quality for New Power System - Bijun LI; Wei LI; Xijian DONG (Zhongguo dianli, 2024)
In the context of new power system, the safe and stable operation of power system is more dependent on the control-based system security and stability service. The ex-post and ex-ante entire-process evaluation of service response is an essential technical support to realize the effective management and control of the control-based system security and stability service quality. To address the common problems in assessing the control-based system security and stability service quality, this paper analyzes the characteristics of the control-based system security and stability service, and determines the connotation and factors for assessing the control-based system security and stability service quality, including service equipment quality and service resource quality before service response, as well as the service response quality after service response. The criteria, index system, methodology and basic data for assessing the control-based system security and stability service quality are described. Finally, an online assessment framework for control-based system security and stability service quality is proposed, including collecting basic data from power plants and substations, determining the assessment criteria and indexes for quality elements, evaluating the indexes and levels for stability services quality, which has universal applicability to the quality assessment of various control-based system security and stability services, including entire key links and complete functional information.